Local and remote physical processes driving variability of the planktonic system in the Juan Fernández Archipelago: A multidisciplinary framework providing conservation insights. Issue 2 (14th February 2021) - Parada, Carolina; Ernst, Billy; Cornejo‐Guzmán, Sebastián; Santa Cruz, Francisco; Sandoval Belmar, Marco; Rivara, Pablo; Tapia, Braulio; Gauthier, Stéphane; Pino‐Aguilera, Josefa; Escribano, Ruben; Morales, Carmen E.
Abstract: The Juan Fernandez Ridge, a vulnerable marine ecosystem located far off the coast of central Chile and formed by several seamounts, guyots and three islands (Robinson Crusoe, Santa Clara and Alejandro Selkirk), has recently been declared a Coastal Marine Protected Area of Multiple Uses with several National Parks embedded in it. Recent studies have highlighted the influence of remote and local oceanographic structures on the hydrographic dynamics of this ridge. However, there is still a gap in understanding how they affect the structure and dynamics of the surrounding insular planktonic communities. A hydroacoustic and oceanographic survey was conducted during the austral spring (October 2016), including hydrographic and zooplankton sampling around Robinson Crusoe Island. Oceanographic features were identified and tracked using satellite data (chlorophyll‐a (Chl‐a) and sea surface temperature) and modelling results. Two events of Chl‐a increase relative to a threshold (>0.45 mg m −3 ) were forced by different physical processes, both affecting the western side of Robinson Crusoe Island. In event A during the cruise period, Chl‐a subsurface maxima were associated with the arrival of a coastal meander originating on the continental shelf off Chile (remote process); the zooplankton was dominated by copepods and salps, with an evident coastal–oceanic gradient. In event B, Chl‐a maxima were linked to a local upwelling forced by the intensification of a localized SSW wind. No influence of remote eddies or local Von Kármán vortices on Chl‐a distribution was observed. These findings highlight the influence of remote and local physical processes on the structure of planktonic communities around Robinson Crusoe Island. Understanding the variability of these mechanisms and their effects at the base of the pelagic food web is critical in adopting an ecosystem‐level approach.